Future Scenario of Spatiotemporal Changes in Land Use and Land Cover Using CA-Markov Model, GIS and Remote Sensing Applications - Ibrahim A. Farhan; Mohd. S. Mahafdah; Edlic Sathiamurthy; Lina A. Salameh; Hind Sarayreh (Migration Letters, 2023)
In Jordan’s Balqa governorate, spatiotemporal changes in land cover between 1984 and 2022 were examined using satellite imagery. This study analyzed the observed and future LULC (land use and land cover) patterns, with a focusing on agricultural land areas, urban land expansion, and rapid population growth. GIS, remote sensing analysis tools, CA-Markov model were employed, and satellite images of Landsat 5 TM, 8 OLI, and 9 OLI2 for the years 1984, 1994, 2004, 2014, and 2022 were used to analyze and explore LULC characteristics. Statistical analysis were performed using the Kendall correlation matrix on observed and expected LULC. The results revealed a significant increase in the total built-up area from 16.29 km2 to 54.6 km2 during the study period with an expected sharp increase of 112.7 (106.3%) in the next four decades, i.e.2050s. The study also indicated that urban sprawl was random and accompanied by increasing demand for residential land use. In addition, there was a significant decrease in the barren land, and rangeland and arable land in favor of urban expansion with a rate of change of 40.1% (r=-0.944; p=0.001) and 38.2% (r=-0.889; p=0.001), respectively. Meanwhile, the area of mixed agricultural will continue to increase and reach 392.6 km2 (220.1%) during the period 1984-2060.This study recommends that urban management should implement a comprehensive national policy, enforcing stricter regulations for urban land use patterns, and enacting new legislation.